Application of control theory in inventory and order based production control system (IOBPCS - Ariffin, Saparudin (Penerbit UTM Press, 1992)
The use of efficient production and inventory control systems is of great importance for industry. This paper gives a review of the research by Towill [1] concerning control theory application in an inventory and order based production control systems (IOBPCS). This paper studies the ability of such Inventory System to recover from shock demands and to protect the manufacturing process from random sales variations. Some simulation results are plotted. One good compromise design achieved has the time-to-adjust inventory, demand averaging time and production delay time all of comparable magnitude.